Attitudes towards Artificial Intelligence in Medical Education and Practice among Undergraduate Medical Students at a Public Medical School in Sarawak, Malaysia - Chau Chung, Chai; Md Mizanur, Rahman; Karen Shendy, Sampson Sambong; Siti Nursyazwani, Azmi Murad; Hariz Hizami, Hatta; Chai Zi, Penny Chen (Faculty of Medicine, Universiti Kebangsaan Malaysia, 2024)
Introduction: Artificial intelligence (AI) is revolutionising medical education and practice, making it essential to understand medical students’ attitudes toward AI for curriculum development. However, the attitudes of medical students in Sarawak, Malaysia, toward AI remain underexplored.